Synthesis and Characterization of Chitosan Based Graft Copolymers with Binary Vinyl Monomers for Controlled Drug Release Application - Devi, Lalita; Kr. Sharma, Rajeev; P. Singh, Anirudh (Drug Delivery Letters, 2015)
Background: Chitosan is a semi-synthetic biopolymer obtained by the alkaline deacetylation of chitin by the use of concentrated NaOH. It exhibits excellent biological properties such as biocompatibility, bioactivity biodegradation in the human body, immunological, antimicrobial and wound-healing activity. Chitosan is a unique amino carbohydrate, as it has dual-functionality as hydroxyl and amino groups in it. It is soluble in dilute acidic media and insolubility of chitosan in basic media confines its biomedical applications as cannot interact with the cationic amenities. So as to increase its locale of biomedical applications the graft modification of chitosan is becoming progressively more imperative for developing smart materials based on this amino polysaccharide. Methods: In this current work, we have synthesized and characterized the graft copolymers of chitosan grafted with binary monomer mixture of acrylic acid with other vinyl monomers like acrylamide and acrylonitrile by free radical initiation method. The binary graft copolymers were investigated for swelling at different pH in order to define their end uses in the sustainable and controlled release of anti-inflammatory drug, Diclofenac sodium (DS). Results: The synthesized graft copolymers were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermal analysis (TGA/DTA), scanning electron microscopy(SEM) and swelling studies. It is observed that the sorption of drug on polymeric samples is directly linked with swelling properties of polymeric samples. Ch-gpoly( AAc-co-AAm) load maximum drug in it as it swell maximum in all solutions of different pH. Conclusion: Graft copolymers were also studied for the sustainable release of anti-inflammatory drug, diclofenac sodium as a function of time and pH and found that polymeric samples Ch-g-poly(AAc-co-AAm) showed best results for sustained drug release.
Keywords: Characterization